Financial management training for the community of Karimunjawa Village Jepara - Diah Kusuma, Chusnu Syarifa; Kumoro, Joko; Kistianingsih, Isti; Hanafi, Mochamad (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2025)
The Community Service Program in Karimunjawa Village, Jepara, Central Java, aims to improve the understanding and skills of family financial management among housewives. The problem is addressed through three stages of activities: preparation, implementation, and evaluation. The preparation stage involves conducting a preliminary survey to assess field conditions, followed by training and mentoring. The methods used include lectures, question-and-answer sessions, and discussions. The results of the training program indicate that 90% of participants successfully understand basic financial concepts, while 89% of them have a good understanding of family financial planning and management. Furthermore, 71% of participants successfully implemented effective family financial management practices after receiving guidance from the facilitators.